A aqueous binder for secondary batteries and a positive electrode slurry for secondary batteries to which it is applied

KR1020260135618APending Publication Date: 2026-09-14KOREA ELECTRIC POWER CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020250028429
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2026-09-14

Smart Images

  • Figure PAT00001_ABST
    Figure PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a water-based binder for a secondary battery and a secondary battery positive electrode slurry to which the same is applied, and more specifically, to a water-based binder that enables the manufacture of an environmentally friendly electrode by using the water-based binder.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a water-based binder for a secondary battery and a secondary battery positive electrode slurry to which the same is applied, and more specifically, to a water-based binder that enables the manufacture of an environmentally friendly electrode by using the water-based binder. Background Technology

[0002] Globally, the reduction of power generation using conventional fossil fuels and the expansion of renewable energy sources such as solar and wind power are being gradually implemented to achieve carbon neutrality. Korea has also established a carbon neutrality goal and roadmap for 2050 and is making steady efforts to expand renewable energy generation. However, as renewable energy is an energy source with high variability depending on climate and region, the construction and operation of large-scale Energy Storage Systems (ESS) capable of reinforcing the existing grid are essential for a stable power supply using it. Currently, the ESS market is dominated by lithium-ion batteries developed for conventional electric vehicles. While some commercialized ESS technologies exist, such as NaS and VRFB, they are facing difficulties in market expansion due to lower economic efficiency and performance compared to lithium-ion batteries.

[0003] Lithium-ion batteries have limitations, including the continuous occurrence of fire accidents due to the use of flammable materials, high costs resulting from the use of metals with limited reserves and regional concentrations as primary materials, and significant price volatility. Accordingly, research and development on low-cost and safe ESS technologies capable of overcoming the limitations of existing lithium-ion batteries is continuously being conducted, and among these, aqueous secondary batteries using aqueous electrolytes are attracting attention as an alternative. Unlike lithium-ion batteries that use organic solutions as electrolytes, aqueous secondary batteries use aqueous electrolytes, making them fundamentally free from the risk of ignition and fire; their performance and characteristics are determined by the materials of the positive and negative electrodes.

[0004] Among the aqueous secondary batteries known to date, the zinc-manganese dioxide aqueous secondary battery is a next-generation battery composed of a manganese dioxide anode, a zinc cathode, and a zinc sulfate aqueous electrolyte. It offers the advantage of lower manufacturing costs compared to lithium-ion batteries because the main materials are inexpensive metals such as manganese dioxide and zinc, which are abundant in reserves, and the manufacturing environment does not require moisture control, resulting in low energy consumption during the process. However, due to the low energy density and lifespan characteristics resulting from the use of an aqueous electrolyte, improvements in energy density and lifespan are necessary for the commercialization of the technology.

[0005] The core materials constituting a secondary battery are the anode, cathode, electrolyte, and separator; among these, the anode is a critical component that determines the battery's theoretical capacity and voltage. The anode consists of an active material that participates in the battery's electrochemical reactions, a conductive material to enhance electrode conductivity, and a binder that bonds the components to form an electrical network within the electrode. Particularly for secondary batteries, where electrode structure changes accompany continuous charging and discharging, the selection of the binder is crucial for stable operation and long lifespan.

[0006] Organic PVdF (Polyvinylidene Fluoride) binders are currently used in the manufacture of electrodes for most rechargeable batteries, including lithium-ion batteries. As a fluorine-based polymer, PVdF binder is widely used as a binder for rechargeable batteries due to its excellent chemical stability with respect to organic electrolytes and superior electrochemical stability, which prevents decomposition even in high voltage ranges. However, since PVdF binder was developed for lithium-ion batteries with high operating voltages and organic electrolyte systems, high interfacial resistance between the electrode and electrolyte and low adhesion between the electrode and current collector are causes of poor lifespan characteristics in aqueous rechargeable batteries using aqueous electrolytes. Furthermore, since PVdF binder is used in solution form by dissolving PVdF powder in NMP solvent, the use of NMP solvent is essential for the dispersion and mixing of electrode materials. NMP (N-Methyl-2-Pyrrolidone) is an expensive and toxic organic solvent, so the application of a binder that can replace PVdF binders is necessary for the development of low-cost and eco-friendly water-based secondary batteries. Prior art literature

[0007] Republic of Korea Published Patent Application No. 10-2024-0069981 The problem to be solved

[0008] The objective of the present invention is to provide an aqueous secondary battery that enables the manufacture of an eco-friendly electrode by using a water-based binder and using water as a solvent for the anode material, and has improved lifespan characteristics through low interfacial resistance between the electrode and the electrolyte and high adhesion between the electrode and the current collector. means of solving the problem

[0009] To achieve the above objective, a water-based binder according to one embodiment of the present invention comprises a water-based solvent; and CMC (Sodium-Carboxymethyl Cellulose), and further comprises SBR (Styrene-Butadiene Rubber).

[0010] In addition, the secondary battery positive electrode slurry of the present invention comprises a positive electrode active material; a conductive material; and an aqueous binder of claim 1 or 2.

[0011] The above active material may be one or more selected from the group consisting of α-MnO2, β-MnO2, γ-MnO2, and ε-MnO2.

[0012] The above conductive material may be one or more selected from the group consisting of graphite, carbon nanotubes, graphene, and carbon black.

[0013] The viscosity can be 1,000 to 4,000 cp. Effects of the invention

[0014] The present invention has the effect of improving the lifespan characteristics of an aqueous battery through low interfacial resistance between the electrode and the electrolyte and high adhesion between the electrode and the current collector due to the use of an aqueous binder.

[0015] In addition, by using a water-based binder in the manufacture of aqueous battery cathodes, water can be used as a solvent for the cathode material, which has the effect of enabling the production of an environmentally friendly electrode. Brief explanation of the drawing

[0016] Figure 1 shows a photographic image of the adhesion analysis of an anode using a water-based binder according to one embodiment of the present invention. Figure 2 illustrates the results of a cycle capacity analysis of a coin cell with an anode using a water-based binder according to one embodiment of the present invention. FIGS. 3a to 3c illustrate the results of electrochemical impedance measurements of a coin cell with an anode using a water-based binder according to one embodiment of the present invention. FIG. 4 shows a photographic image of a disassembled anode after 200 cycles of charging and discharging of a coin cell with an anode using a water-based binder according to one embodiment of the present invention. Specific details for implementing the invention

[0017] Hereinafter, embodiments of the present invention are described in detail so that those skilled in the art can easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.

[0019] A water-based binder according to one embodiment of the present invention comprises a water-based solvent; and CMC (Sodium-Carboxymethyl Cellulose).

[0020] The above aqueous solvent may be one or more selected from the group consisting of distilled water (DI-Water), ethanol (Ethanol), isopropanol (IPA), n-propanol (n-Propanol), butanol (Butanol), ethylene glycol (EG), propylene glycol (PG), diethylene glycol (DEG), acetic acid, and citric acid.

[0021] Unlike the PVdF binder that makes surface contact, the above CMC (Sodium-Carboxymethyl Cellulose) makes point contact on the binder, resulting in a uniform distribution of the binder and fewer contact points with the electrode active material, which leads to excellent formation of electron and ion conduction networks. Additionally, by forming carboxylic acid in an aqueous solution, it creates strong hydrogen bonds, thereby improving the adhesion between the current collector and the electrode active material (positive active material).

[0023] In addition, the water-based binder according to one embodiment of the present invention further comprises Styrene-Butadiene Rubber (SBR). The Styrene-Butadiene Rubber (SBR) provides flexibility to the binder, strengthens adhesion, and improves bonding with carbon materials as a conductive material.

[0025] In addition, the secondary battery positive electrode slurry of the present invention comprises a positive electrode active material; a conductive material; and an aqueous binder of claim 1 or 2.

[0026] The above active material may be one or more selected from the group consisting of α-MnO2, β-MnO2, γ-MnO2, and ε-MnO2.

[0027] The above conductive material may be one or more selected from the group consisting of graphite, carbon nanotubes, graphene, and carbon black.

[0028] The viscosity of the anode slurry can be 1,000 to 4,000 cp.

[0030] The present invention will be described in detail below through examples. The following examples are intended only to aid in understanding the invention and do not limit the scope of the invention.

[0032] Example 1. Preparation of Water-based Binder (CMC)

[0033] 16.5 g of CMC (Sodium-Carboxymethyl Cellulose) was added to 1,303.5 g of distilled water and completely dissolved while stirring at room temperature at 500 rpm for 3 hours to prepare an aqueous binder solution.

[0035] Example 2. Preparation of water-based binder (CMC / SBR)

[0036] A water-based binder solution was prepared by adding 16.5 g of CMC and 33 g of SBR (Styrene-Butadiene Rubber) aqueous solution (50 wt% with H2O) (16.5 g of SBR) to 1,270.5 g of distilled water and completely dissolving them while stirring at 500 rpm for 3 hours at room temperature.

[0038] Example 3. Preparation of an anode using an aqueous binder (CMC) solution

[0039] 297 g of the positive active material β-MnO2 and 16.5 g of carbon black (Super P) were added to the binder solution of Example 1 and stirred at room temperature at a speed of 500 rpm for 6 hours to prepare a positive slurry, and the positive slurry was coated to a thickness of 50 μm on a 0.02 mm thick stainless steel foil and then dried in a 60°C oven for 24 hours to prepare a positive.

[0041] Example 4. Preparation of an anode using an aqueous binder (CMC / SBR) solution

[0042] 297 g of the positive active material β-MnO2 and 16.5 g of carbon black (Super P) were added to the binder solution of Example 2 and stirred at room temperature at a speed of 500 rpm for 6 hours to prepare a positive slurry, and the positive slurry was coated to a thickness of 50 μm on a 0.02 mm thick stainless steel foil and then dried in a 60°C oven for 24 hours to prepare a positive.

[0044] Comparative Example 1. Preparation of organic PVdF binder

[0045] An organic binder solution was prepared by adding 16.5 g of PVdF (Polyvinylidene Flouride) to 148.5 g of NMP (N-Methyl-2-Pyrrolidinone) and completely dissolving it while stirring at 500 rpm for 12 hours at room temperature.

[0047] Comparative Example 2. Preparation of an electrode using an organic PVdF binder

[0048] 297 g of the positive active material β-MnO2 and 16.5 g of carbon black (Super P) were added to the binder solution of Comparative Example 1 and uniformly mixed while stirring at room temperature at a speed of 500 rpm for 6 hours to prepare a positive slurry, and the positive slurry was coated to a thickness of 50 μm on a stainless steel foil with a thickness of 0.020 mm and then dried in an oven at 60°C for 24 hours to prepare a positive.

[0050] Experimental Example 1. Measurement of Binder Viscosity

[0051] The viscosity of the binder solutions prepared in Example 1, Example 2 and Comparative Example 1 was measured at 30, 60, and 100 rpm using a rotational viscometer, and the measurement results are summarized in Table 1 below.

[0052] rpm Example 1 Example 2 Comparative Example 1 30 4,800 cp 4,210 cp 1,173 cp 60 3,445 cp 2,997 cp 1,013 cp 100 2,573 cp 2,278 cp 928 cp average 3,606 cp 3,161 cp 1,038 cp

[0053] Referring to Table 1, the aqueous binder solutions in Examples 1 and 2 exhibited higher viscosity compared to the PVdF binder solution in Comparative Example 1, and it was confirmed that the CMC / SBR binder solution in Example 2 had a slightly lower viscosity compared to the CMC binder solution in Example 1.

[0055] Experimental Example 2. Measurement of viscosity of anode slurry using binder solution

[0056] The viscosity of the anode slurry in Example 3 and Comparative Example 2 was measured at 30, 60, and 100 rpm using a rotational viscometer, and the measurement results are summarized in Table 2 below.

[0057] rpm Example 3 Comparative Example 3 30 3,115 cp 4,203 cp 60 2,288 cp 2,240 cp 100 1,763 cp 1,440 cp average 2,388 cp 2,628 cp

[0058] Referring to Table 2, at low rpm (30 rpm), the viscosity of the anode slurry using PVdF binder (Comparative Example 2) was higher than that of the anode slurry using CMC binder (Example 3), but at high rpm (60, 100 rpm), the viscosity of the anode slurry using CMC binder (Example 3) was higher, and when the average viscosity of the two anode slurries was calculated, it was confirmed that they showed similar viscosity.

[0060] Experimental Example 3. Measurement of the adhesion strength of the electrode (anode)

[0061] To verify the adhesion strength of the anodes prepared in Examples 3, 4, and Comparative Example 2, the ASTM D3359 test method was performed, and the cross-cut grid size was set to 1 mm in width and 1 mm in height. According to the adhesion strength classification criteria, the adhesion strength is classified from 0B to 5B, and as the number increases from 0B to 5B, the adhesion strength becomes stronger. Photographic images of the adhesion strength analysis of the anodes are shown in Figure 1, and the adhesion strength analysis results are summarized in Table 3 below.

[0062] Example 3 Example 4 Comparative Example 2 test 4B 4B 0B

[0063] Referring to Table 3, it was confirmed that the adhesion strength of the anodes using water-based binders in Examples 3 and 4 was superior to that of the anode using PVdF binder in Comparative Example 2, and the adhesion strength of the anode using CMC binder (Example 3) and the anode using CMC / SBR binder (Example 4) showed the same result.

[0065] Analysis Example. Capacity test of coin cell according to charge and discharge cycles

[0066] In order to fabricate a coin cell using the anodes prepared in Examples 3 and 4 and Comparative Example 2, the electrodes were cut into circular disc shapes and used as anodes, the cathode was a 250 μm zinc metal plate, the separator was a glass fiber, and the electrolyte was an aqueous solution in which a mixed salt of 2.0 M ZnSO4 + 0.1 M MnSO4 was dissolved to fabricate a CR2032 type coin cell.

[0068] Experiment 4. Capacity test of coin cell according to charge and discharge cycles

[0069] The coin cell fabricated in the above analysis example was subjected to a charge and discharge cycle capacity test under constant current conditions by applying a current of 0.1 A / g (0.3C) in a voltage range of 1.0 to 1.85, and the analysis results are shown in FIG. 2. In FIG. 2, the coin cell using the anode of Example 3 is labeled "CMC", the coin cell using the anode of Example 4 is labeled "CMC+SBR", and the coin cell using the anode of Comparative Example 2 is labeled "PVdF".

[0070] As shown in Figure 2, the coin cell using the anode of Comparative Example 2 using a PVdF binder exhibited discharge capacities of 183.9, 99.8, 106.9, 104.3, 101.2, 98.0, 93.5, 89.0, and 79.9 mAhg at 1, 5, 10, 15, 20, 25, 30, 35, 40, and 45 cycles, respectively. On the other hand, in the case of a coin cell using the anode of Example 3 using a CMC binder, discharge capacities of 200.3, 144.7, 132.3, 138.3, 143.5, 148.7, 153.4, 157.6, 157.5, and 157.3 mAh / g were exhibited at 1, 5, 10, 15, 20, 25, 30, 35, 40, and 45 cycles, respectively. In the case of a coin cell using the anode of Example 4 using a CMC / SBR binder, discharge capacities of 194.6, 106.8, 117.0, 131.5, 139.9, 144.0, 149.0, 152.8, 154.6, and 157.4 mAh / g were exhibited at 1, 5, 10, 15, 20, 25, 30, 35, 40, and 45 cycles, respectively. It was confirmed that the capacity retention rate after 45 cycles compared to 1 cycle was 43.4% for the coin cell with PVdF binder (anode of Comparative Example 2), 78.5% for the coin cell with CMC binder (anode of Example 3), and 80.8% for the coin cell with CMC / SBR binder (anode of Example 5), and that the lifespan characteristics were significantly improved when using an aqueous binder compared to when using a PVdF binder.

[0072] Experimental Example 5. Measurement of Electrochemical Impedance of a Coin Cell

[0073] To analyze the resistance components of the battery according to the type of binder, the coin cell fabricated in the above analysis example was subjected to impedance analysis in the frequency range of 200 kHz to 100 MHz. To observe changes in resistance characteristics according to charge and discharge cycles, the results of 1 cycle and 20 cycles were compared and are shown in FIGS. 3a to 3c. When the Nyquist impedance curve is plotted as shown in FIGS. 3a to 3c, different sizes of semicircles can be observed depending on the type of binder. This represents charge transfer resistance, a phenomenon that occurs when charge moves at the electrode interface; the larger the size of the semicircle, the greater the charge transfer resistance. The size of the semicircle is largest for the coin cell using a PVdF binder (anode of Comparative Example 2; FIG. 3c), followed by the coin cell using a CMC binder (anode of Example 3; FIG. 3a), and the size of the semicircle decreases in the order of the coin cell using a CMC binder (anode of Example 4; FIG. 3b). Through this, it was confirmed that when using an aqueous binder, the resistance at the electrode-electrolyte interface is lower compared to a PVdF binder.

[0075] Experimental Example 6. Disassembly of coin cell after 200 charge and discharge cycles, and observation of positive electrode.

[0076] After performing 200 cycles of charging and discharging under constant current conditions by applying a current of 0.1 A / g (0.3C) at a voltage range of 1.0 to 1.85 V to the coin cell fabricated in the above analysis example, the coin cell with the anode of Example 3 and the coin cell with the anode of Comparative Example 2 were disassembled and their respective anodes were observed, and photographic images of each disassembled anode are shown in FIG. 4.

[0077] As shown in Fig. 4, in the case of the anode using a CMC binder (Example 3), it was confirmed that there is less detachment of the electrode from the current collector due to continuous charging and discharging, as the strong adhesion and holding power between the electrode and the current collector compared to the anode using a PVdF binder (Comparative Example 2).

[0079] Although preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements by those skilled in the art using the basic concept of the present invention as defined in the following claims also fall within the scope of the present invention.

Claims

Claim 1 A water-based solvent; and a water-based binder comprising CMC (Sodium-Carboxymethyl Cellulose). Claim 2 A water-based binder according to claim 1, further comprising SBR (Styrene-Butadiene Rubber). Claim 3 A water-based secondary battery positive electrode slurry comprising a positive electrode active material; a conductive material; and a water-based binder of claim 1 or 2. Claim 4 A water-based secondary battery positive electrode slurry according to paragraph 3, wherein the active material is one or more selected from the group consisting of α-MnO2, β-MnO2, γ-MnO2, and ε-MnO2. Claim 5 A water-based secondary battery anode slurry according to paragraph 3, wherein the conductive material is one or more selected from the group consisting of graphite, carbon nanotubes, graphene, and carbon black. Claim 6 A water-based secondary battery positive electrode slurry having a viscosity of 1,000 to 4,000 cp in paragraph 3.